Financial Development and Poverty: Case Study of Thailand - Lerskullawat, Attasuda; Puttitanun, Thitima (Journal of Applied Economics and Management Strategy, 2023)
This study examines the effect of financial development in both banking and capital market development on poverty in Thailand using 77 provincial data from 2007 to 2020 at the country levels and all regions of Thailand, namely, the Northern, the Central, the Northeastern, and the Southern. Using panel data model with fixed/random effect, this study finds that financial development, both in banking sector and capital market development, reduce poverty in Thailand and at the regional-level in Thailand, especially in the Northern and North-eastern regions compared to other regions which have lower effect or insignificant effect. The result can lead to policy implications for government in planning economic and social development, as well as financial development strategies in the future.